Historical Perspectives on Economic Change: Culture, Economy, and Social Transformation - Challoumis, Constantinos; Eriotis, Nikolaos; Vasiliou, Dimitrios (Journal of Cultural Analysis and Social Change, 2026)
This research examines the role of culture as a mediating force in long-run processes of economic transformation and social change. Moving beyond purely economic explanations of structural change, it integrates insights from political economy, institutional economics, and historical sociology to analyze how cultural drivers shape economic trajectories across distinct stages of development. The analysis adopts a historical and comparative scope, focusing on three broad phases of transformation: the transition from agrarian to commercial economies, industrialization and labor reorganization, and the contemporary era of services and financialization. Five core cultural drivers—religion and ethics, education and knowledge, social norms, institutions, and technology adoption—are examined through an inductive, non-empirical methodology based on historical narratives and cross-stage synthesis rather than econometric estimation. Their relative influence is assessed using an ordinal framework and summarized through conceptual heatmaps and quadrant visualizations. The findings indicate that cultural drivers operate in differentiated and stage-specific ways: education and technology adoption emerge as structurally transformative in advanced stages of development; social norms function as key mediating mechanisms shaping coordination and governance; institutions play a predominantly supportive and enabling role; and religion and ethics remain context-dependent, exerting indirect influence rather than disappearing in modern economies. Overall, the study demonstrates that culture is not a static determinant of economic outcomes but a dynamic and reconfiguring force that evolves alongside economic structures, conditioning the paths through which economies transform over time.